Diagnostic Value of Portal Vein Velocity for Portal Hypertension in Patients with Hepatitis B Virus-related Cirrhosis - Liu, Changchun; Chen, Sizhe; Yan, Xinwen; Xiang, Yi; Hui, Jialiang; Liu, Zhao; Yu, Qiang; Li, Yongwu; Qi, Ruping; Liu, Yuan; Bai, Xu; Gao, Yuanzhi; et al. (Current Medical Imaging, 2021)
Background: Portal vein velocity (PVV) has shown a reasonable correlation with the presence of portal hypertension in patients with cirrhosis. This study aims to evaluate the value of PVV for diagnosing clinically significant portal hypertension (CSPH) and predicting the risk of variceal hemorrhage (VH) in patients with hepatitis B virus (HBV)-related cirrhosis. Materials and Methods: A cohort of 166 consecutive adult patients with HBV-related cirrhosis was recruited in this retrospective study from two high-volume liver centers in China between April 2015 and April 2017. The performance of PVV and other non-invasive parameters for diagnosing CSPH and predicting the risk of VH was studied. Results: PVV demonstrated the best performance for diagnosing CSPH (defined as an HVPG ≥10 mmHg) in patients with HBV-related cirrhosis among the included non-invasive predictors with the area under the receiver operating characteristic curve (AUC), specificity, and sensitivity of 0.745, 50%, and 93.5%, respectively. Other non-invasive markers, including APRI, AAR, LS, FIB-4, and diameter of the portal vein, did not show sufficient performance with the AUCs of 0.565, 0.560, 0.544, 0.529, and 0.474, respectively. With regard to predicting the risk of VH (defined as an HVPG ≥12 mmHg), PPV also exhibited a moderate performance with an AUC of 0.762, which was superior to that of the aforementioned markers. By using two cutoff values of PVV to rule-out (11.65 cm/s) and rule-in (20.20 cm/s) CSPH, 30 (33.7%) patients showed definite results categories, with 23 (76.7%) patients were well classified and 7 (23.3%) were misclassified. Fifty-nine (66.3%) patients were with indeterminate results. By using PVV values of 13.10 cm/s and 21.40 cm/s to rule-out and rule-in HVPG ≥ 12mmHg, 34 (38.2%) patients has definite results, among whom 26 (76.5%) were well classified and 8 (23.5%) were misclassified. And 55 (61.8%) patients required further evaluation. Conclusion: PPV is insufficient to serve as a non-invasive parameter for identifying CSPH and predicting the risk of VH in patients with HBV-related cirrhosis.
Keywords: Hepatic venous pressure gradient